Dari hati: a public speaking initiative for non-academic staf - Sahlan, Noraziah (Faculty of Medicine, 2023)
In August 2023, the Clinical Laboratories Department (CDL) launched a public speaking program among the non-academic staff. The program dubbed Dari Hari aimed mainly to build and boost self-confidence among the non-academic staff in CDL. The program was scheduled to be held once a fortnight, and all CDL staff comprises science officers, medical laboratory technologies, clerks, and health attendants who will take turns to share and deliver a topic of their choosing for 15-20 minutes at 08:30 in the morning to their colleagues. The topics can be from various fields of interest or knowledge